2016
DOI: 10.33697/ajur.2016.025
|View full text |Cite
|
Sign up to set email alerts
|

A Relationship Between Time Perception and State-Anxiety

Abstract: Participants in this study were randomly assigned to one of three interval groups of either one, three, or five minutes. All participants were asked to estimate a group-assigned time interval and complete the state portion of the State Trait Anxiety Inventory (STAI). It was hypothesized that higher levels of state anxiety would cause participants to overestimate the passage of time. It was also hypothesized that shorter interval durations would be estimated more accurately than longer interval durations. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Moreover, regression analysis also failed to be significant for the audio and video accuracy indexes, suggesting that audio and video time estimation probably referred to different processing circuits, partially distinct from the interoceptive system. These results are supported by recent literature (Mioni et al, 2016 ) according to which time perception in depression showed inconclusive results (Thones and Oberfeld, 2015 ) along with not-inductive time studies in anxiety that also provided mixed results (Lueck, 2007 ; Brown, 2016 ).…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, regression analysis also failed to be significant for the audio and video accuracy indexes, suggesting that audio and video time estimation probably referred to different processing circuits, partially distinct from the interoceptive system. These results are supported by recent literature (Mioni et al, 2016 ) according to which time perception in depression showed inconclusive results (Thones and Oberfeld, 2015 ) along with not-inductive time studies in anxiety that also provided mixed results (Lueck, 2007 ; Brown, 2016 ).…”
Section: Discussionsupporting
confidence: 81%